Critical insights into the reinforcement potential of cellulose nanocrystals in polymer nanocomposites. Issue 4 (August 2019) - Miao, Chuanwei; Hamad, Wadood Y.
Highlights: Cellulose nanocrystals are polar, negatively-charged hydrophilic nanoparticles. CNCs have high crystallinity and stiffness. CNCs can exceptionally reinforce certain polymer nanocomposites. CNCs can act as effective nucleating agents, and improve cross-linking capacity. CNCs have a promising potential for industrial, biomedical and sports applications. Abstract: Cellulose nanocrystals (CNCs) are highly polar, negatively-charged hydrophilic nanoparticles extracted from biomass through acid hydrolysis. They have high crystallinity and stiffness, as well as exceptional capability in reinforcing some polymer nanocomposites. While these remarkable improvements are limited to a certain class of polymers under strict conditions, CNCs can contribute to improving nanocomposite performance via other means, such as nucleating effect or cross-linking capacity. In this review, we offer critical insights into the reinforcing mechanism(s) of CNC-polymer nanocomposites and the factors that influence their performance. We aim to provide answers to the following questions: (1) how do CNCs contribute to nanocomposite reinforcement via percolation theory; (2) how to form a percolated CNC network in a CNC-polymer nanocomposite; (3) what are the factors affecting CNC performance and how do they work; and (4) how can we take advantage of CNC's attributes to create high-performance nanocomposites?